ANALISIS PENGARUH TINGKAT PARTISIPASI ANGKATAN KERJA (TPAK) DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP KEMISKINAN (Studi Kasus Di 10 Kabupaten Kota Di Aceh Dengan Kemiskinan Tertinggi Tahun 2020) - Nurhaila, Nurhaila; anwar, khairil (LPPM UNIMAL, 2024)
This study aims to determine the effect of labor force participation, human development index (HDI) on poverty in the 10 urban districts with the highest poverty in 2020. The data used in this research is data obtained from the Central Statistics Agency. The analysis method used is panel data regression using the E-views10 program. The research results show that partially the labor force participation rate variable is negative and significant on poverty, the human development index variable has a significant and significant effect on poverty. Simultaneous research results, the labor force participation rate variable and the human development index have a significant effect on poverty. The coefficient of determination (R2) is 0.938870, which means that the influence of the labor force participation rate and human development index on poverty is 0.938870 or 93.88% while the remaining 6.12% is influenced by variables outside this research.